Spaces $S^p$ with Nonsymmetric Metric - Rukasov, V. I.; Stepanets, O. I. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We determine exact values of the best approximations and Kolmogorov widths of $q$-ellipsoids in spaces $S_φ ^{p,μ}$ defined by anisotropic metric.